Ten New Dammarane-Type Saponins with Hypolipidemia Activity from a Functional Herbal Tea—Gynostemma pentaphyllum - Yin, Maojing (Molecules, 2020)
Gynostemma pentaphyllum (thumb.) Makino is a functional herbal tea commonly used in Asian countries and regions to reduce blood lipid levels. G. pentaphyllum saponin is the main component, but there are still a large number of components with lipid-lowering activity that have not been found. In this study, 10 novel dammarane-type saponins, (1–10) and a known one (11) were isolated from G. pentaphyllum. Ten new compounds were identified and named as yunnangypenosides A-J (1–10), and another known one (11) was also obtained. Their chemical structures were determined by MS, NMR spectroscopic analyses. Moreover, the cytotoxicities on human HepG-2 hepatocellular carcinoma cells of these isolates were evaluated, and the results showed that compounds 1–11 had no obvious cytotoxicity. Finally, all these compounds were evaluated for their lipid-lowering effect by means of the oil red O staining method. Ten compounds could significantly reduce lipid levels except of 2, especially 8 exhibite the strongest hypolipidemia activity.